Pengaruh Perlakuan Kimia Alkalinasi dan Asetilasi terhadap Kekuatan Tarik dan Mikrostruktur Serat Abaka - Muhammad Ichsanudin; Imam Prabowo; Mochamad Mussoddaq; Mochamad Chalid (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
Today, environmental problems, especially soil pollution due to inorganic waste or waste that does not decompose, are a major problem and need to be solved, especially in developing countries with high populations such as Indonesia. One of the causes of soil pollution problems is the use of inorganic fibers such as glass fiber and carbon fiber. The use of materials that are not environmentally friendly in the industry will cause environmental problems due to nature's inability to decompose the glass fiber material in nature. The focus of this research is to reduce environmental pollution by using natural fibers such as abaca fiber as an alternative to inorganic fibers. This is due to its properties, namely: low density, good specific strength, low price, and a high biodegradable ability so that it can reduce glass fiber or carbon fiber waste that does not decompose. To support this, abaca fiber needs to be hydrophobic so that it becomes compatible with other materials when combined together with other materials. One of the ways that can be done is by alkaline chemical treatment and acetylation using KOH and CH3COOH. Chemical treatment was carried out by dipping abaca banana fibers into a solution of alkaline compounds and acetylated compounds KOH and CH3COOH with a concentration of 5 M and 10 M for 4 hours. After chemical treatment, the abaca banana fibers were characterized for mechanical properties using ASTM D 3379 standards to determine the tensile strength of the fibers and using an optical microscope to determine the microstructure of the abaca fibers.